Anatomical pattern of entheseal and synovial fibroblast activation in patients with psoriasis and its risk of developing psoriatic arthritis - Corte, Giulia; Atzinger, Armin; Temiz, Selahattin Alp; Noversa de Sousa, Rita; Mutlu, Melek Yalcin; Schönau, Verena; Raimondo, Maria Gabriella; Kleyer, Arnd; Kuwert, Torsten; Ramming, Andreas; Simon, David; Sticherling, Michael; et al. (RMD Open, 2024)
OBJECTIVES: To assess the presence and anatomical distribution of activated fibroblasts in the joints and entheses of patients with psoriasis with arthralgia and to test how fibroblast activation visualised by 68gallium-labelled fibroblast activation protein inhibitor-04 (68Ga-FAPI-04)-positron emission tomography (PET)/CT correlates with clinical tenderness, musculoskeletal ultrasound findings and progression to psoriatic arthritis (PsA). METHODS: We conducted a prospective cohort study in patients with psoriasis and arthralgia who underwent clinical and ultrasound evaluation and whole-body PET/CT imaging with 68Ga-FAPI-04. 68Ga-FAPI-04 uptake at synovial and entheseal sites was assessed by maximal standardised uptake values (SUVmax) and PET/CT Joint Index (JI); logistic regression models were used to investigate its correlation with clinical and ultrasound findings. Survival analyses were performed on patients with at least 6 months of follow-up. RESULTS: 36 patients with psoriasis were enrolled. 68Ga-FAPI-04 uptake was found in 318 (7.9%) joints and 369 (7.3%) entheses in 29 (80.6%) participants, with a mean SUVmax (SD) of 3.2 (1.8) for joints and 2.9 (1.6) for entheses. Large joints and the lower limbs were predominantly affected. A significant positive relationship was found between 68Ga-FAPI-04-PET/CT signal intensity and the 68 tender joint count (SUVmax: p<0.001; PET/CT-JI: p<0.001) and tender entheses count (SUVmax: p<0.001; PET/CT-JI: p=0.002). No correlations were found with ultrasound findings (SUVmax: p=0.969; PET/CT-JI: p=0.720). Patients with relevant synovio-entheseal 68Ga-FAPI-04 uptake showed a statistically significant higher risk of developing PsA (p=0.02), independent of ultrasound findings. CONCLUSIONS: Patients with psoriasis presenting with arthralgia show localised signs of resident tissue activation in joints and entheses, which are associated with higher risk of developing PsA.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Fibroblasts; Outcome Assessment; Health Care; Psoriatic Arthritis; Risk Factors; Ultrasonography

IL-1 Inhibitors in the Treatment of Familial Mediterranean Fever: Treatment Indications and Clinical Features in a Large Real-World Cohort - Yalcin-Mutlu, Melek; Icacan, Ozan Cemal; Yildirim, Fatih; Temiz, Selahattin Alp; Fagni, Filippo; Schett, Georg; Tascilar, Koray; Minopoulou, Ioanna; Burul, Gokhan; Bes, Cemal (Journal of Clinical Medicine, 2024)
Background: The accruing evidence about the efficacy of anti-IL-1 agents in Familial Mediterranean Fever (FMF) patients led to their widespread off-label use. Therefore, identifying precise indications and clinical characteristics of IL-1i-warranting patients are important. This study investigated the clinical characteristics and treatment indications of patients with FMF requiring interleukin 1 inhibition therapy (IL-1i). Methods: Hospital records of FMF patients attending a tertiary care center at the Department of Rheumatology, University of Health Sciences, Basaksehir Cam and Sakura City Hospital were retrospectively analyzed. Data on symptoms and disease manifestations, age of symptom onset, time to diagnosis, MEFV variants, type of treatment, and their indications were collected. Results: Between June 2020 and March 2023, 312 FMF patients were identified. The mean age at the onset of symptoms was 14.0, and the mean time to diagnosis was 11.9 years. In total, 87.1% of patients were receiving colchicine monotherapy, while the remaining 11.8% warranted IL-1i. Clinical symptoms and flare manifestations did not show a significant difference between the two groups. However, patients receiving IL-1i started having symptoms at younger age (11.5 vs. 14.5, p = 0.042) and time to diagnosis was longer (18.2 vs. 11.0, p < 0.01). M694V homozygosity was more common in patients receiving IL-1i. Indications for patients receiving IL-1i were colchicine resistance (8.0%), secondary amyloidosis (5.1%), and colchicine intolerance (2.2%). Conclusions: This study shows that a subset of FMF patients, particularly those with a more severe phenotype with an earlier disease onset and M694V homozygosity, require IL-1i treatment despite the overall good efficacy and tolerability of colchicine, primarily due to colchicine resistance, intolerance, or complications such as amyloidosis.
CRIS-Team Scopus Importer:2024-07-12
Keywords: amyloidosis; colchicine intolerance; colchicine resistance; familial mediterranean fever; interleukin-1 inhibitors

Incomparable regional prevalence estimates of Neuromyelitis Optica due to lack of standardization: Comment on the article by Taskiran et.al. - Temiz, Selahattin Alp; Tascilar, Koray (Multiple Sclerosis and Related Disorders, 2025)
CRIS-Team Scopus Importer:2025-05-02

Paucity of viral infection symptoms in patients with immune-mediated inflammatory diseases. - Yalcin-Mutlu, Melek; Kleyer, Arnd; Krönke, Gerhard; Fagni, Filippo; Temiz, Selahattin Alp; Meder, Christine; Dietrich, Peter; Orlemann, Till; Mößner, Johanna; Schönau, Verena; Bohr, Daniela; Schuster, Louis; et al. (BMJ Open, 2025)
OBJECTIVES: Although patients with immune-mediated inflammatory diseases (IMID) are thought to be more susceptible to viral infections, it is unclear whether their presentation differs between patients with IMID and healthy controls. This study aimed to investigate the symptom pattern of common viral infections in patients with IMID and compare it with controls without IMIDs. DESIGN: A cross-sectional study conducted between 1 February and 30 April 2020, using a questionnaire. SETTING: Seven tertiary regional care centers in Germany, which specialised in the care of patients with IMID (namely, in gastroenterology, dermatology, rheumatology and immunology clinical care). PARTICIPANTS: One thousand nine hundred nine participants completed the survey (757 patients with IMID; 1152 non-IMID controls). PRIMARY OUTCOME MEASURE: The occurrence of 11 common viral illness symptoms within the preceding 3 months in patients with IMID and non-IMID controls. RESULTS: Symptom data were clustered, based on number and co-occurrance, into 3 major clusters and 2 subclusters ranked by the average number of symptoms. Patients with inflammatory bowel disease and psoriasis were significantly overrepresented in the lower-frequency subcluster of the polysymptomatic cluster. Patients with rheumatoid arthritis were overrepresented in the lower-frequency subclusters of the intermediate and oligo-/asymptomatic clusters. Controls were over-represented only in the higher-frequency subclusters of each major cluster where none of the IMIDs were over-represented. Spondyloarthritis and other IMIDs were also overrepresented in the low-frequency subcluster, but the results were not significant. Overall, patients with rheumatoid arthritis patients reported fewer symptoms (rate ratio=0.68, 95% CI, 0.59 to 0.80) than non-IMID controls. CONCLUSION: Patients with IMID are over-represented in low-frequency subclusters, even among individuals who have reported a broad range of viral infection symptoms. This pattern suggests that the manifestations of viral infections are different between patients with IMID and controls, thus challenging the accurate and early diagnosis of infections.
EVALuna2:581658

Rheumatic? A diagnostic decision support tool for individuals suspecting rheumatic diseases: Mixed-methods usability and acceptability study - Jakobi, Stefan; Boy, Katharina; Wagner, Magali; May, Susann; Temiz, Selahattin Alp; Liphardt, Anna-Maria; Araujo, Elizabeth; Carmona, Loreto; Knevel, Rachel; Schett, Georg; Knitza, Johannes; Muehlensiepen, Felix; et al. (BMC Rheumatology, 2025)
Background: The early diagnosis of inflammatory rheumatic diseases (IRDs) is of paramount importance in order to prevent irreversible damage to joints and to optimize treatment outcomes. Nevertheless, conventional care pathways frequently entail diagnostic delays spanning several months. Symptom checkers (SCs) have the potential to provide a solution by offering validated symptom assessments, improving triage systems and expediting diagnostic evaluations. The objective of this mixed-methods study is to assess the usability and acceptability of the SC Rheumatic? among individuals with suspected rheumatic diseases. Methods: A total of 105 individuals with suspected IRDs who were newly presenting at an outpatient rheumatology clinic completed the Rheumatic? symptom checker and an evaluation questionnaire. The questionnaire comprised the System Usability Scale (SUS) and Net Promoter Score (NPS). Additionally, 14 participants were interviewed by telephone in order to gain further insights through the qualitative method. Results: The Rheumatic? symptom checker received a “good” usability score, with an average SUS of 78 ± 16 (range 0-100). Younger participants reported significantly higher usability scores (p < 0.03). However, the NPS was − 15 (range − 100 to 100), indicating lower acceptability. Qualitative data supported the positive usability ratings but emphasized the need for enhancements to increase user engagement and perceived value, such as a current perceived lack of immediate benefit for many users. Their experience varied in terms of impact, with some patients suggesting an increased awareness of their symptoms while others did not notice any difference. Conclusion: Rheumatic? demonstrates good usability, particularly among younger users. Interviews revealed valuable suggestions for improvements, which could enhance overall acceptability and user satisfaction. Implementing Rheumatic? could lead to more efficient triage, potentially reducing diagnostic delays and an optimized allocation of resources. Future iterations should prioritize implementation strategies to maximize user impact and benefit. Clinical trial number: Not applicable.
CRIS-Team Scopus Importer:2025-05-30
Keywords: Arthritis; eHealth; Health services research; NPS; Symptom checkers; Telemedicine; Triage; Usability; Usability study

Screening for psoriatic arthritis in dermatological settings-are handheld ultrasound devices the gamechangers we hoped for? - Bartsch, Vanessa; Fagni, Filippo; Krieter, Manuel; Ibrahim, Mohammed; Temiz, Selahattin Alp; Yalcin-Mutlu, Melek; Schett, Georg; Simon, David; Hueber, Axel (Rheumatology, 2024)
EVALuna2:551954